Distinguishing Entailment and Presupposition Under Negation Test - Indarti, Gatri Asti Putri (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2015)
Distinguishing entailment from presupposition is quite difficult because their semanticrelation seems to be similar. Both entailment and presupposition have an automaticrelationship based on the context. However, those semantic relations can still bedifferentiated by using negation test to show whether a pair is entailment or presupposition.This research focuses on sentences and utterances. Thus, this research aims to analyze andtest pairs of entailment and pairs of presupposition by using negation in utterances. Thedata were twelve comic strips from the Internet and they were analysed by using a negation test. The analysis shows that negation test is useful to test entailment and presupposition inthe comic strips. It can be concluded that the difficulty of distinguishing pair of entailmentand presupposition in the comic strip using negation test has been successfully solved. Inthis case, negation test is suitable to test entailment and presupposition. This research canbe developed further by other researchers to distinguish entailment and presupposition byusing another test if the negation test cannot be used to any further extent.